Estrategia didáctica “Adivina adivinador y serás buen lector” y su influencia en el aprendizaje de la lecto – escritura en el área de comunicación, en los niños/as de 5 años de la I.E 288 del distrito de Rioja - Chamoly Fernández, Lupita (2012)
The didactic strategy Divining and you will be good reader based you configured a sequence of processes in the use of the riddles like: Oral, written and graphic presentation; Phonological and written deduction, syllabic and phonological disintegration, integration of sounds and intensive practice; For the sake of raising the learning of the lecto-escritura in the area of communication in the boys and girls of five years of the l. E. N 288 of Rioja's district. lt was necessary te turn te fact-finding background and theoretic contributions like the theory of the linguistic intelligence and sociological theory for your realization, the same that they allowed formulating and te contrast the factfinding hypothesis: lf we applied the didactic strategy the Fortuneteller guesses and you wi/1 be good reader, then the learning of the lecto-escritura in the area of communication is raised significantly. The study fits te the kind of applied investigation, experimental patterned level quasi experimental, whose coverage comprises the boys and girls of five years and 20 boys' and girls' sign; Whom administrated a pre their test te diagnose his lecto-escritura's level befare the application of strategy and ene behind test te determine the happened changes after the application of the didactic strategy. The named instrument lecto-escritura's test that was administrated te the sign of study enabled gathering relevant information whose data they were prosecuted in electronic intervening form the Software SPSS v17 and checkered presentees and graphics constructed according te standards established for investigation. Right after interpretation, analysis and discussion of the results, the alternative hypothesis meaning that. You Guess the application of the didactic strategy Divining was accepted And you will be good reader, you have lifted lectoescritura's level in the boys and girls of five years of the 1 significantly. E. N 288 of Rioja's district raising the average of 9. 70 in the pretest te 15.50 in the behind test; For which your application in another ene is recommended institutions of jurisdiction.